1997
DOI: 10.1002/(sici)1097-0045(19970601)31:4<223::aid-pros3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor levels in cancer cells and in sera of patients suffering from proliferative disorders of the prostate

Abstract: BACKGROUND Both benign and malignant growth of the prostate depend on the induction of a microvasculature. Basic fibroblast growth factor (bFGF), a potent angiogenic factor, is thought to play an important role in this process. METHODS bFGF expression in prostatic carcinoma was assessed by ELISA, reverse transcription polymerase chain reaction, and immunohistochemistry. RESULTS DU‐145 and PC‐3 tumor cells produced bFGF. Almost 80–90% of it was localized in the cytoplasm, and 10–20% was associated with extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 41 publications
(56 reference statements)
6
55
1
1
Order By: Relevance
“…The high molecular weight isoforms possess the NH 2 -terminal nuclear localization signal and are exclusively localized to the nucleus (19)(20)(21). Recent data indicate that increased expression of bFGF promotes tumorigenic and metastatic properties of various malignancies including prostate cancer and is associated with inferior survival of prostate cancer patients (2,3,19,(21)(22)(23)(24)(25)(26). Furthermore, loss of even one allele of bFGF in the transgenic adenocarcinoma of the mouse prostate model increases their survival by suppressing metastasis (27).…”
Section: Introductionmentioning
confidence: 62%
“…The high molecular weight isoforms possess the NH 2 -terminal nuclear localization signal and are exclusively localized to the nucleus (19)(20)(21). Recent data indicate that increased expression of bFGF promotes tumorigenic and metastatic properties of various malignancies including prostate cancer and is associated with inferior survival of prostate cancer patients (2,3,19,(21)(22)(23)(24)(25)(26). Furthermore, loss of even one allele of bFGF in the transgenic adenocarcinoma of the mouse prostate model increases their survival by suppressing metastasis (27).…”
Section: Introductionmentioning
confidence: 62%
“…Whereas FGF-2 production in early tumors is confined to stromal cells, in advanced prostate cancer FGF-2 is overproduced by tumor cells (Giri et al, 1999;Kwabi-Addo et al, 2004). Of note, in prostate cancer cell lines, the levels of FGF-2 and FGFR1 have been shown to increase proportionally to the degree of cancer aggressiveness and castration resistance (Nakamoto et al, 1992;Cronauer et al, 1997). The analysis of tumor specimens has shown that enhanced FGF signaling results in increased proliferation, invasiveness and resistance to therapy in several solid and hematological malignancies (Menzel et al, 1996;Konig et al, 1997;Song et al, 2000;Sezer et al, 2001;Acevedo et al, 2009;Turner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In early tumor lesions, aberrant FGF-2 production and expression of its receptor (FGFR1) can alter the epithelial/stromal communication, which ensures the balance between growth and renewal of the epithelial compartment under physiological conditions (KwabiAddo et al, 2004). Moreover, FGF-2 production by both stromal and tumor cells promotes increased proliferation and metastasis formation in prostate cancer (PCa) (Cronauer et al, 1997;Giri et al, 1999;Yang et al, 2008). Thus, the FGF-2/FGFR axis is an attractive target for cancer therapy, in terms of both ligand sequestration and receptor inhibition (Smith et al, 2001;He et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3 Growth factors that promote angiogenesis include bFGF and VEGF 165 , 6,7 both of which are produced by neoplastic cells. 9,10,12 LfcinB inhibited bFGF-and VEGF 165 -induced, but not nonheparin-binding EGF-induced, angiogenesis in the in vivo Matrigel plug assay. Although it is possible that trace amounts of undefined proangiogenic factors that remain in growth factor-reduced Matrigel might have influenced our results, we believe this to be unlikely because very little endothelial cell infiltration was detected in Matrigel plugs that did not contain exogenous bFGF or VEGF 165 .…”
Section: Discussionmentioning
confidence: 99%
“…8 bFGF is also expressed by many human cancer cells, including prostate carcinoma and melanoma cells and is believed to be important for the formation of tumor vasculature. 9,10 VEGF is a specific mitogen for vascular endothelial cells that is produced by a variety of cell types, including activated macrophages and cancer cells. 10 -12 Alternate mRNA splicing of the VEGF gene product gives rise to four different VEGF isoforms, 13 including the VEGF 165 isoform that binds heparan sulfate.…”
mentioning
confidence: 99%